Modeling the Bioaccumulation and Biomagnification Potential of Microplastics in a Cetacean Foodweb of the Northeastern Pacific: A Prospective Tool to Assess the Risk Exposure to Plastic Particles - Alava, Juan José (Frontiers in Marine Science, 2020)
Microplastics (MPs) can readily be ingested by marine organisms. Direct ingestion and trophic transfer are likely to be the main pathway for microplastics to bioaccumulate in upper trophic level organisms. Bioaccumulation potential of MPs in marine mammalian foodwebs is scarcely known. To understand whether microplastics bioaccumulate in marine mammals, a bioaccumulation model for MPs was developed for the filter-feeding humpback whale and fish-eating resident killer whale foodwebs of the Northeastern Pacific. Applying three concentration scenarios for MPs by entering observed water and sediment concentrations as input data (low, high and moderate scenarios), and tested under two different elimination rates (kE) for zooplankton, the model predicted species-specific and foodweb-specific bioaccumulation potential. The predator-prey biomagnification factor (BMFTL, used to assess the ratio of the MP concentration in predator to that in prey adjusted to the difference of trophic levels), involving cetaceans, appeared to be not only lower than one or equal to one (BMFTL ≤ 1 as in resident killer whale/Chinook salmon), but also BMFTL > 1 in some predator-prey relationships (humpback whale/zooplankton). Depending on the magnitude of abiotic concentrations used in the modelling, the trophic magnification factor (TMF) regression analyses over time showed lack of evidence for trophic magnification as the magnification was independent of the trophic level, indicating no changes (TMF = 1; p>0.05), and trophic dilution (TMF<1; p<0.05) due to the decrease in MP concentrations as the trophic level increased. Projected biomagnification in simplified foodwebs revealed no significant increase in concentrations as the trophic level increased (TMF=1; p>0.05), following 100-365 days. Compared to the high biomagnification behaviour of persistent organic pollutants in marine foodwebs, scarce biomagnification capacity of microplastic was predicted in the cetacean foodwebs. Notwithstanding, the moderate to high microplastic bioaccumulation predicted in some lower trophic level marine organisms highlights the health risks of toxic exposure to marine fauna and coastal communities relying strongly on seafood. This modelling work provides a tool to assess the bioaccumulation potential and impact of microplastics in the marine environment to support risk assessment and inform plastic waste management.